The Malay Moros In The Philippines: Ethnicity, Religious Identity And Globalization - Angeles, Viviene SM. (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The article traces the evolution of Malay Moro identity in the Philippines, the globalizing effects of resisting Spanish and American colonization on transforming their Muslim religion from an ethnic religion into a global identity, and the transition of the once despised thirteen Muslim ethno-linguistic groups into a symbol of resistance. Colonialism served a globalizing function in cementing Moro identity and paved the way for a unified Muslim anti-government resistance in post independence Philippines. Globalizations also increased Moro identification with the wider ummah.